MENINGKATKAN KOMPETENSI PENGELOLAAN PEMBELAJARAN GURU BAHASA INGGRIS SEKOLAH DASAR MELALUI KEGIATAN KELOMPOK KERJA GURU - ZULHERMINDRA ZULHERMINDRA (Ta'dib, 2014)
The teaching of English at elementary school level is believed to give promising contribution since it can improve students’ language proficiency at early stages. However, teachers’ professional competency is suspected as one of potential problems due to the facts that some of them are not really prepared to teach at this level. Even most of the teachers are not English teaching background. Realizing the phenomena, continuous training and knowledge upgrading programs should be of prior concern. This article is therefore intended to share some ideas how to improve elementary English teachers’ professional competency, especially in designing syllabus and develepoing lesson plan by considering the nature ofvelepoing lesson plan by considering the nature of young learners and the principles of teaching them as well.Kata kunci: kompetensi, pengelolaan pembelajaran, guru, bahasa Inggris, KKG